Learning Video Media Using Dynamic Drawing Principles for Vocabulary Recognition to Improve Early Childhood Speaking Comprehension - Ni Luh Elin Widianingsing (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
There are obstacles to low student learning outcomes. This is caused by teachers who only use the lecture method in the learning process, which results in students not playing an active role in the learning process. This research aims to create learning video media using the principle of dynamic drawing for vocabulary introduction to improve speaking comprehension for young children in group B kindergarten. The media development process follows ADDIE procedures. The data collection method uses a questionnaire, while the instrument uses a rating scale of 1-5. Data analysis was carried out using descriptive statistical methods and quantitative descriptive statistics to describe the average scores from experts regarding the learning video media being developed. The research results show that this learning video passed the validity and practicality tests well, with a "very good" assessment from media experts, material experts, teachers, and students. Thus, this learning video based on dynamic drawing principles is effective in increasing young children's understanding of storytelling, making a positive contribution in the context of multicultural education, and has the potential to become a reference for developing similar products in the future. This research implies that dynamic drawing-based learning video media has great potential to support early childhood learning, especially in understanding animal vocabulary.